Advances in research on the relationship between mitochondrial function and colorectal cancer: a bibliometric study from 2013 to 2023 - Liu, Jinhui; Chang, Yonglong; Ou, Qinling; Chen, Linzi; Yan, Haixia; Guo, Duanyang; Wang, Chongjie; Zhang, Sifang (Frontiers in Immunology, 2024)
The study provides a thorough examination of literature from 2013 to 2023, delving into the intricate relationship between mitochondrial function and colorectal cancer (CRC). It offers a concise overview of the current landscape and emerging trends in this rapidly evolving research area. The findings indicate a consistent rise in annual publications, reflecting growing interest and significant potential in the field. China emerges as the leading contributor, followed by the United States and India. However, despite China’s dominance in output, its average citation rate is lower than that of the US, which leads in citations per publication, highlighting a noticeable disparity. In the realm of research institutions, Shanghai Jiao Tong University and China Medical University are identified as major contributors, yet the potential for inter-institutional collaboration remains largely untapped, suggesting avenues for future synergy. Internationally, China-US collaborations are particularly robust, fostering cross-border knowledge exchange. Hyun Jin Won and Li Wei are recognized as prolific authors, while Ahmedin Jemal is an influential co-cited scholar, noted for his seminal contributions. Keyword analysis reveals research focus areas, such as the complex CRC tumor microenvironment, molecular mechanisms of oxidative stress, and key multidrug resistance pathways. It also highlights the promising potential of mitochondria-targeted therapies and nanomolecular technologies in clinical practice, signaling their growing significance in addressing complex health challenges. The study underscores the imperative to validate complex mitochondrial mechanisms and signaling pathways in CRC, with a particular emphasis on translating these insights into drug targets for clinical trials. Advancing this research is expected to refine and enhance CRC treatment strategies. Additionally, it highlights the urgency of validating mitochondrial complexities in CRC, advocating for collaborative efforts to link these mechanisms with tailored therapeutic interventions for clinical testing. This integrated approach promises significant advancements in developing effective, targeted CRC treatments, ultimately improving patient outcomes.